Investigation of tetracycline and degradation products in Euphrates river receiving outflows of trout farms - Topal, Murat; Topal, Emine Isil Arslan (Wiley, 2016)
In this study, tetracycline (TC), epitetracycline (ETC), 4-epianhydrotetracycline (EATC) and anhydrotetracycline (ATC) concentrations were determined in the surface waters carrying outflows of trout farms. The samples were taken from downstream of Keban Dam and upstream of Karakaya Dam Lake, which are located in the Euphrates and Tigris River Basin. The occurrence of TC and degradation products (DPs) was proved in the sampling points which take the outflows of the trout farms. Tetracycline and DPs were under the detection limits in sampling points where the trout farms do not exist. The highest TC concentration was detected as 50.0 +/- 2.5 mu g L-1 (1st week), whereas the lowest TC concentration was 8.2 +/- 0.41 mu g L-1 (7th week). The highest ETC concentration was 88.1 +/- 4.4 mu g L-1 (3rd week) and the lowest ETC concentration was 9.4 +/- 0.4 mu g L-1 (3rd week). The highest and lowest EATC concentrations were detected as 35.8 +/- 1.8 mu g L-1 (2nd week) and 8.2 +/- 0.4 mu g L-1 (2nd week) respectively. The highest ATC concentration was 28.3 +/- 1.4 mu g L-1 (3rd week), whereas the lowest was 6.54 +/- 0.34 mu g L-1 (7th week). Tetracycline and DP concentrations detected in surface waters followed the following order: ETC>TC>EATC>ATC.
Keywords: trout farm; surface water; tetracycline; degradation product; dam lake; Euphrates-Tigris